PENGARUH JENIS DAN DOSIS KOMPOS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT PADA TANAH ALUVIAL - BUNIA CERI; Radian; Dini Anggorowati (JURNAL BORNEO AKCAYA, 2023)
Tomato plant (Lycopersicum esculentum Mill.) is a horticultural plant with lots of vitamins that are beneficial to the human body. In some areas, tomato plants are cultivated on alluvial soils. However, it turns out that alluvial soil has soil characteristics that are poor in nutrient content, so it requires composting to increase the nutrient content of the soil in order to increase tomato plant production. This study aims to determine the effect of the type and dosage of compost on the growth and yield of tomato plants in alluvial soil. This study used a completely randomized design (CRD) consisting of 2 factors and 3 replications. The first factor was the type of compost (mixed weeds, empty oil palm bunches, water hyacinth, and krinyu), and the second factor was the dose of compost, which consisted of four treatment levels (160 g/polybag ≈ 5 t/ha, 320 g/polybag ≈ 10 t /ha, 480 g/polybag ≈ 15 t/ha, and 640 g/polybag ≈ 20 t/ha). The results of this study showed that the type and dosage of compost had a significant effect on the vegetative phase of tomato plants (plant height, number of leaves, leaf area, and plant dry weight); however, the type and dosage of compost had no significant effect on the generative phase of tomato plants (number of fruits and fruit).